Dark blue [videorecording (DVD)] - Ayer, David; Ellroy, James, 1948-; Chubb, Caldecot; Russell, Kurt; Gleeson, Brendan; Speedman, Scott (MGM, 2026)
Set during the tense times of the LA riots, the film tells the story of Eldon Perry, veteran officer of the Los Angeles Police's special investigation squad as he tutors a new police officer who comes to learn the depth of corruption in his own police department.